Mobile Application Design for Ordering Clean Water Using UCD Method in Indonesia - Watomakin, Dominikus Boli; Pramajuri, Baltra Agusti; Suyoto, Suyoto (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Clean water is an essential basic requirement for humans. In eastern Indonesia, especially the provinces of East Nusa Tenggara (NTT), Maluku and Southeast Sulawesi, the need for clean water is quite urgent. The socio-cultural conditions, geographical conditions, low rainfall levels, and the distribution of freshwater from the Regional Water Company (PDAM) is still not right. Communities in the three provinces utilise clean water buying and selling services using tank cars to fulfil their daily needs for clean water in reservoirs and water tanks. Orders still use telephone or SMS, so it seems slower. Thus the design of mobile ordering applications for clean water was proposed in this study and was named Go-Water. With the Go-Water app, users can order clean water by choosing the closest shelter model and driver, and then the order is forwarded to the driver for processing. The User-Centered Design (UCD) method use for Go-Water application design. The Go-Water application can help users to order clean water quickly and help improve business quality for service providers. The results of the usability perspective analysis on the Go-Water application design obtained an average percentage of 83%. The result shows the design of the Go-Water app, can be accepted according to user needs. The contribution in this study is the design of the proposed mobile application centred on the user, previously there was no system for ordering 5,000 litres and 6,000 litres of clean water using a tank car and the price offered was more beneficial for both parties.